Transition in morphology and properties in bottom-up HPHT nanodiamonds synthesized from chloroadamantane - Stehlik, Stepan; Belsky, Petr; Kovarik, Tomas; Nemeckova, Zuzana; Henych, Jiri; Ukraintsev, Egor; Vlk, Ales; Ledinsky, Martin; Ekimov, Evgeny (Nanoscale advances, 2025)
Direct bottom-up high pressure high temperature (BU_HPHT) synthesis of nanodiamonds (NDs) from organic precursors excels in the ability to control the size of the resulting BU_HPHT NDs via the temperature of the synthesis. Here we investigated size-dependent thermal, colloidal, and structural properties of the BU_HPHT NDs and focused on the transition in morphology and properties occurring at around 900 °C (≈2 nm). Using transmission electron microscopy, small angle X-ray scattering and atomic force microscopy we show that the sub-900 °C samples (<2 nm NDs) do not have nanoparticle character but 2D platelet morphology with sub-nm unit thickness. Correspondingly, sub-900 °C samples (<2 nm NDs) have a negative zeta potential and hydrophobic character and should be considered as a form of a molecular diamond. The above-900C (>2 nm NDs) samples have nanocrystalline character, positive zeta potential and are dispersible in water similarly to other types of hydrogenated NDs. By in situ Raman spectroscopy experiments, we show that the transition is also related to the structural instability of the oxidized sub-2 nm BU_HPHT NDs.